Microstructural investigation of as cast and PREP atomised Ti-6Al-4V alloy - (:unkn) unknown (MANEY PUBLISHING, 2011)
A microstructure characterisation of Ti-6Al-4V is conducted for cast, extruded and micrometre sized particles. The plasma rotating electrode process is used to produce spherical Ti-6Al-4V powders from an alloy electrode. The process parameters and their impact on the material properties are described. The effects of electrode rotation speed on the particle size distribution, particle shape and crystal structure are investigated in detail. Optical microscopy and scanning electron microscopy are used for microstructural characterisation. The analysis shows that cast and extruded Ti-6Al-4V alloys have equiaxial alpha and alpha+beta phase structures, while plasma rotating electrode processed powder from the same alloy compositions has an acicular or martensitic (alpha) structure. The microstructure scale depends on the particle size. Microhardness measurements are used to assess mechanical property dependence on the microstructure of this alloy. The rapidly cooled alloy particles have much higher hardness than cast or extruded bulk alloy.
Keywords: Solidification; Microstructural characterisation; Ti-6Al-4V powders; PREP atomisation; MECHANICAL-PROPERTIES; BEHAVIOR; TI6AL4V